The tempest [Búrka anglicky] - Shakespeare, William, 1564-1616; Shakespeare, William, 1564-1616.; Macaw Books (Leicester : Sweet Cherry Publishing, 2020)
The Tempest is one of the most popular plays of William Shakespeare. The play is set on a remote island inhabited by Prospero, the banished Duke of Milan, and his daughter, Miranda. Prospero, now a magician, uses his magic to control the spirits of the island. With the help of the spirit Ariel, he conjures a tempest in the sea to draw in his brother, Antonio, and Alonso, King of Naples, who had unlawfully stolen his dukedom. The play revolves around Prospero´s attempt to restore himself and his daughter to their rightful position.
A short narrative version of the play has been suitably adapted to help to introduce the play to young readers.
Keywords: Fathers and daughters -- Pictorial works -- Juvenile fiction; Shipwreck victims -- Pictorial works -- Juvenile fiction; Children's stories -- Pictorial works; čítam si sám (7+); cudzojazyčná literatúra